Glutamine and leukemia research: progress and clinical prospects - Zexin Wang; Miao Liu; Qiang Yang (Discover Oncology, 2024)
Abstract Leukemia is an abnormal proliferation of white blood cells that occurs in bone marrow and expands through the blood. It arises from dysregulated differentiation, uncontrolled growth, and inhibition of apoptosis. Glutamine (GLN) is a "conditionally essential" amino acid that promotes growth and proliferation of leukemic cells. Recently, details about the role of GLN and its metabolism in the diagnosis and treatment of acute myeloid, chronic lymphocytic, and acute lymphoblastic leukemia have emerged. The uptake of GLN by leukemia cells and the dynamic changes of glutamine-related indexes in leukemia patients may be able to assist in determining whether the condition of leukemia is in a state of progression, remission or relapse. Utilizing the possible differences in GLN metabolism in different subtypes of leukemia may help to differentiate between different subtypes of leukemia, thus providing a basis for accurate diagnosis. Targeting GLN metabolism in leukemia requires simultaneous blockade of multiple metabolic pathways without interfering with the normal cellular and immune functions of the body to achieve effective leukemia therapy. The present review summarizes recent advances, possible applications, and clinical perspectives of GLN metabolism in leukemia. In particular, it focuses on the prospects of GLN metabolism in the diagnosis and treatment of acute myeloid leukemia. The review provides new directions and hints at potential roles for future clinical treatments and studies.